Analysis of Halal Tourism Destination Development in Madura - Bambang Haryadi; Hery Purwanto; Merry Satya Angraini; Fachrur Rozi; Allyvia Camelia (Faculty of Economics and Business, University of Mataram, 2024)
The purpose of this study is to analyze the carrying capacity and the development of halal tourism destinations using the Business Model Canvas approach. The study was conducted in ten halal tourism destinations from August to November 2023. Primary and secondary data were used in this research. The results of the study indicate that the carrying capacity for halal tourism development is quite adequate. The results of the BMC element mapping, ten halal tourism destinations in Madura have provided value to tourists. All efforts fulfill the nine BMC elements. The results of the BMC mapping with SWOT show the strategies that can be carried out: 1) support for marketing development, 2) support for destination development, 3) support for the development of small and medium industries (IKM) in tourist destinations, and 4) institutional support. Based on the SWOT analysis, there are strategies that can be carried out, namely: 1. Integrating infrastructure development by building linkages with halal tourism destinations, 2. Establishing laws and regulations in the region, and 3. Providing ease of doing business for the community, 4. Tourism destination managers can take advantage of their advantages.